HOST RANGE AND CROSS INFECTIVITY STUDIES OF CORYNESPORA CASSIICOLA - D. PRASANTH KUMAR,; S.L. BHATTIPROLU,; G. BINDU MADHAVI,; CH. CHIRANJEEVI, (The Journal of Research ANGRAU, 2024)
Corynespora infecting cotton has wide host range and due to its importance in blackgram earlier in Andhra Pradesh an investigation was carried to test the ability of the pathogen, Corynespora cassiicola isolated from cotton could cross infect blackgram crop and vice versa. Isolates were collected from the major cotton and blackgram (B-1 to B-6) growing areas viz., Guntur, Prakasam and Krishna districts. Experimental design was completely randomized in a factorial arrangement of 12x3x2 (12 isolates, 3 areas and 2 hosts) and replicated thrice. Cross inoculation experiments demonstrated variation in the level of latent period, infectivity and per cent disease index (PDI) among C. cassiicola isolates. The incubation period was 4 to 7 days in cotton for cotton isolates with highest PDI (32.94) in C-5 and lowest in C-2 isolates (20.77 PDI). It was 3 and 6 days in blackgram with blackgram isolates; the highest PDI (38.05) was recorded in B-1 and lowest in B-6 (16.06). However, C6 (8.28) and B5 (11.21) displayed the highest virulenceindex, respectively. Cross infectivity studies registered the highest PDI with C3 isolate (24.82) and the lowest in C5 isolate (12.48) in blackgram; whereas PDI was highest with B2 isolate (15.90) and B6 isolate (5.59) in cotton. In terms of virulence, C1 (4.50) and B4 (2.44) exhibited the highest virulence index, respectively.